Tinjauan Konsep Feminisme Pada Bangunan Natasha Skin Care Bandung Sebagai Pusat Kecantikan - Almira Muthi Faliha; Yeptadian Sari (Journal of Architectural Design and Development (JAD), 2021)
The rapid development of the times makes technology more sophisticated, it makes information and communication sources accepted quickly, because of the role of the internet. Its influence on society can have both good and bad impacts for the continuity of life patterns in social interaction. The bad impact that is often experienced by women is usually a feeling of insecurity in their appearance when interacting socially, this problem makes women have to try to find ways so that they can be confident by looking attractive according to their expectations. Therefore, we need a place of beauty center that applies the concept of feminism architecture with feminine characteristics. The case study that will be discussed in this research is Natasha Skin Care, which is located on Jl. Supratman No. 84 Bandung, while the method used is descriptive qualitative. The results of this study can be said that the Natasha Skin Care building is almost close to the application of the concept of feminist architecture according to several criteria, namely in the selection of materials on the facade, the color of the interior and exterior and a clear division of space between public and private spaces.